2011
DOI: 10.3113/fai.2011.1000
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Nonanatomic Tenodesis Reconstruction Methods of Combined Anterior Talofibular Ligament and Calcaneofibular Ligament Deficiency

Abstract: The knowledge of stress inside the ligaments and reconstructed grafts could help to better understand the biomechanical behavior of the reconstructed joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Perenous longus and peroneus brevis tendons are used in the non-anatomical tenodesis. The strength of the reconstructed ligament affects the clinical results [9] . In our study, the correlation was observed between ATFL diameter and peroneal tendon diameters in men, while no correlation was observed in women suggests that the clinical results of these procedures may be more positive in men, but this data should be confirmed by clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perenous longus and peroneus brevis tendons are used in the non-anatomical tenodesis. The strength of the reconstructed ligament affects the clinical results [9] . In our study, the correlation was observed between ATFL diameter and peroneal tendon diameters in men, while no correlation was observed in women suggests that the clinical results of these procedures may be more positive in men, but this data should be confirmed by clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although ankle torsional injuries are commonly treated with non surgical methods, personel treatment options should be considered for athletes engaged in different sports activities [8] . One of the surgical methods is nonanatomic tenodesis and in this method perenous tendons are used [9] . On the other hand, there is no study evaluating the relationship between ATFL diameter and perenous tendon diameter in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these technical difficulties, finite-element modeling technique was developed and has been widely used and validated in the field of foot and ankle surgery. [20][21][22][23][24] The physical validation of the finite-element model of the ankle with respect to contact stress of tibiotalar articular surfaces had been proven with a cadaveric experimental study. 25 Another comprehensive study in this area was published by Haraguchi et al 13 They had performed a study to validate the model of ankle with regard to both contact stresses and ligament tensions in the ankle during walking cycles.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] The physical validation of the finite element model of the ankle regarding contact stresses of tibiotalar articular surfaces had been proved by a cadaveric experimental test. Because of these technical difficulties, a finite element modeling technique was developed, and it has been widely used and validated in the field of foot and ankle studies.…”
Section: Discussionmentioning
confidence: 99%